(untitled) (Temporalis, 2026)
This article, through a literature review, examines criticisms of the assumptions defended by postmodern thought in light of Marx’s theoretical and methodological framework. It presents the problematizations interaction with the theoretical and political inputs of postmodern thought, highlighting the necessary critiques and confrontations, with a view to reaffirming Marx’s critical social theory and its legacy for debates within the profession in Brazil. The analyses focus on clarifying the postmodern theoretical-political tendency’s denial of social totality, universality, and the revolutionary possibility of overcoming the sociability of capital. It argues for an analysis of reality and the profession from the perspective of social totality, considering the theoretical and practical mediations to be highlighted, and confronting the anti-intellectual and pragmatic traits that stubbornly persist in the profession.